(9n-1)+7(n+6)=-60

Simple and best practice solution for (9n-1)+7(n+6)=-60 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9n-1)+7(n+6)=-60 equation:


Simplifying
(9n + -1) + 7(n + 6) = -60

Reorder the terms:
(-1 + 9n) + 7(n + 6) = -60

Remove parenthesis around (-1 + 9n)
-1 + 9n + 7(n + 6) = -60

Reorder the terms:
-1 + 9n + 7(6 + n) = -60
-1 + 9n + (6 * 7 + n * 7) = -60
-1 + 9n + (42 + 7n) = -60

Reorder the terms:
-1 + 42 + 9n + 7n = -60

Combine like terms: -1 + 42 = 41
41 + 9n + 7n = -60

Combine like terms: 9n + 7n = 16n
41 + 16n = -60

Solving
41 + 16n = -60

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-41' to each side of the equation.
41 + -41 + 16n = -60 + -41

Combine like terms: 41 + -41 = 0
0 + 16n = -60 + -41
16n = -60 + -41

Combine like terms: -60 + -41 = -101
16n = -101

Divide each side by '16'.
n = -6.3125

Simplifying
n = -6.3125

See similar equations:

| 3x^2-xy-52y^2=0 | | 3x+2x+7=-41 | | -27=2c-7c-6c | | 3x+1=3x-8 | | 15x+45=120 | | 6(2t-5)=60-6t | | 1/2=3/3 | | 3.75x=21 | | 5x+4x=7 | | 2x-10y=10 | | k=25 | | 16w^2-70w+49=0 | | t+9-3.2=3 | | 8c-72=8c-72 | | 5t+16=11t+4 | | 8x-2=20x+4 | | -6x+4y=-16 | | t+7=-t+5 | | 3n(n-5)-7(3n+9)= | | 16+32x=40x | | 3.89-13=1.4+5 | | 9x^2-2x-11=0 | | 9(12x+6)= | | 3x+4-x=53 | | 2x(x+9)-7X= | | 0.2(0.23-5x)=-0.9x | | -144=18n | | 6(n+3)=12-.12n | | X^3-5x^2-16x+80=0 | | 5x^2-21x+16=0 | | -6(9x-7)=420 | | 1.4z-42=2.8 |

Equations solver categories